GROWTH FORM OF CAREX BIGELOWII GROWING IN SOUTH-CENTRAL ALASKA (EXTENDED ABSTRACT) (15th Symposium on Polar Biology) - キベ, タケシ; マスザワ, タケヒロ; KIBE, Takeshi; MASUZAWA, Takehiro (National Institute of Polar Research, 1994)
P(論文) departmental bulletin paper